Conductive backboard, preparation method thereof and photovoltaic module
By optimizing the composition of the conductive layer material in the conductive backsheet, the problems of poor ductility of the metal conductive layer and mismatch of polymer thermal properties were solved, thereby improving the photoelectric conversion efficiency and mechanical strength of the photovoltaic module and achieving good composite and stability between the conductive layer and the support layer.
Patent Information
- Application Number
- CN202511219291.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-12-05
AI Technical Summary
The existing conductive backsheets have poor ductility, mismatch with the thermal properties of polymers, and poor adhesion, resulting in low photoelectric conversion efficiency of photovoltaic modules.
Conductive adhesives and/or conductive coatings are used as conductive layer materials, including matrix resin, conductive filler, curing agent and solvent. The composition of the conductive layer is optimized by adding metal particles, metal oxides, fibrous materials, carbon-based materials and mica materials to form a continuous conductive network, thereby improving the compositeness and adhesion with the support layer.
It improves the conductivity, mechanical strength, and weather resistance of the conductive backsheet, enhances the photoelectric conversion efficiency of photovoltaic modules, ensures that the conductive layer does not delaminate or peel off during processing and use, and has good ductility and matching with polymer thermal properties.
Smart Images

Figure CN121075728A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photovoltaic module technology, and more specifically, to a conductive backsheet and its preparation method, and a photovoltaic module. Background Technology
[0002] BC cells, also known as back-contact solar cells, are a type of photovoltaic technology that places both the positive and negative electrodes on the back of the cell. This design avoids the shading of sunlight by the front electrodes, as is common in traditional cells, thus improving the cell's photoelectric conversion efficiency and aesthetics.
[0003] Conductive backplanes are a novel material applicable to back-contact packaging. Their structure includes a substrate layer, a conductive layer, and an insulating layer. The conductive layer is the key layer for the conductive backplane to function. Currently, conductive layers generally use only metallic materials; however, metallic conductive layers suffer from poor ductility, mismatch with the thermal properties of polymers, and poor adhesion. Summary of the Invention
[0004] The main objective of this invention is to provide a conductive backsheet and its preparation method, as well as a photovoltaic module, to solve the problems of poor photoelectric conversion efficiency of photovoltaic modules caused by the poor ductility, mismatch between the metal conductive layer and the thermal properties of the polymer, and poor adhesion of the conductive backsheet in the prior art.
[0005] To achieve the above objectives, according to one aspect of the present invention, a conductive backsheet is provided, comprising a support layer, a conductive layer, and an insulating layer stacked sequentially. The conductive layer includes a conductive circuit region, which includes a conductive material, the conductive material being a conductive adhesive and / or a conductive coating. By weight, the conductive material comprises: 20-40 parts of a matrix resin, 50-80 parts of a conductive filler, and 5-10 parts of a curing agent. The conductive filler is selected from any one or more of metal particles, metal oxides, fibrous materials, carbon-based materials, polythiophene polymers, and mica materials with a metal layer on their surface.
[0006] Further, when the aforementioned conductive material is a conductive adhesive, the conductive adhesive comprises, by weight parts: 20-30 parts of a first matrix resin; 60-80 parts of a first conductive filler; 5-10 parts of a first curing agent; 5-15 parts of a first solvent; and 0.1-0.5 parts of a first additive; wherein the first conductive filler is selected from any one or more of first metal particles, a first carbon-based material, and a polythiophene polymer; wherein the first metal particles are selected from any one or more of silver powder, copper powder, and nickel powder; the first carbon-based material is selected from any one or more of graphene, carbon nanotubes, and conductive carbon black; the polythiophene polymer is polythiophene particles; and / or, the resistivity of the first conductive filler is 1.0 × 10⁻⁶. -8 ~3.0Ω·m, preferably 1.17×10-8 ~2×10 -6 Ω·m.
[0007] Further, the first matrix resin is selected from any one or more of epoxy resin, acrylate resin, polyurethane acrylate resin, epoxy acrylate resin, polyurethane resin, polyethylene polyimide resin, silicone resin, and cyanate ester resin; and / or, the resistivity of the first matrix resin is 10 Ω·cm. 11 ~10 18 Ω·m; and / or, the first curing agent is selected from any one or more of amine curing agents, acid anhydride curing agents, imidazole curing agents, and cyanate ester curing agents; wherein, the amine curing agent is selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, m-phenylenediamine, polyamide, dicyandiamide, and amine adducts; the acid anhydride curing agent is selected from any one or more of phthalic anhydride, tetrahydrophthalic anhydride, and methylhexahydrophthalic anhydride; the imidazole curing agent is 2-ethyl-4-methylimidazolium and / or 2-methylimidazolium; and the cyanate ester curing agent is hexamethylene diisocyanate and / or diphenylmethane diisocyanate. ; and / or, the first solvent is selected from any one or more of glycidyl acrylate, butyl glycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, ethyl acetate, propylene glycol methyl ether acetate, acetone, butanone, toluene, xylene, isopropanol, butyl acetate, a mixture of dicarboxylic acid esters, cyclohexanone, 1,4-butanediol, propylene carbonate, γ-butyrolactone, dimethyl silicone oil, n-hexane, petroleum ether, perfluorohexane, hydrogenated naphthalene, and decahydronaphthalene; and / or, the first additive is selected from any one or more of the first defoamer, the first leveling agent, the first plasticizer, and the first antioxidant.
[0008] Further, when the aforementioned conductive material is a conductive coating, the conductive coating comprises, by weight, 30-40 parts of a second matrix resin, 50-60 parts of a second conductive filler, 5-8 parts of a second curing agent, 5-10 parts of a second solvent, and 1-2 parts of a second additive; wherein the second conductive filler is selected from any one or more of second metal particles, metal oxides, second carbon-based materials, fibrous materials, and mica materials with a metal layer on their surface; wherein the second metal particles are selected from any one or more of silver powder, nickel powder, copper powder, iron powder, aluminum powder, and aluminum foil; the metal oxide is selected from any one or more of zinc oxide, lead dioxide, and tin oxide; the second carbon-based material is carbon black and / or graphite; the fibrous material is selected from any one or more of carbon fiber, nickel fiber, copper fiber, and stainless steel fiber; and / or, the resistivity of the second conductive filler is 1.7 × 10⁻⁶. -8 ~3Ω·m, preferably 1.7×10 -8 ~1.5×10 -5 Ω·m.
[0009] Further, the second matrix resin is selected from any one or more of polyacetylene resin, polyaniline resin, polypyrrole resin, polythiophene resin, ABS resin, polyvinyl alcohol resin, fluorocarbon resin, alkyd resin, epoxy resin, phenolic resin, nitrocellulose, cellulose acetate, silicone resin, urea-formaldehyde resin, polyurethane resin, polyvinyl chloride resin, acrylic resin, polyvinylidene chloride resin, polytetrafluoroethylene resin, polystyrene resin, polyethylene resin, polycarbonate resin, and polystyrene resin; and / or, the resistivity of the second matrix resin is 10 Ω·cm. -5 ~10 20 Ω·m; and / or, the second curing agent is selected from any one or more of ethylenediamine, diethylenetriamine, polyamide, Mannich base, phthalic anhydride, maleic anhydride, dicyandiamide, hexamethylene diisocyanate, isophorone diisocyanate, isophorone diisocyanate, benzoyl peroxide, diphenylphosphine oxide, 2-hydroxy-2-methylphenylacetone, aminopropyltriethoxysilane, and platinum catalyst; and / or, the second solvent is selected from any one or more of acetone, butanone, ethyl acetate, butyl acetate, ethanol, isopropanol, toluene, xylene, and ethylene glycol ether; and / or, the second auxiliary agent is selected from any one or more of the second defoamer, second leveling agent, second antioxidant, second plasticizer, and thixotropic agent.
[0010] Furthermore, the conductive material also includes a polymer resin containing a third solvent, wherein the mass percentage of the third solvent in the polymer resin containing the third solvent is 35-45%, and the third solvent is selected from any one or more of xylene, acetone, diester, propylene glycol methyl ether acetate and ethyl acetate; the polymer resin is selected from any one or more of epoxy resin, acrylate resin, polyurethane acrylate resin, epoxy acrylate resin, polyimide resin, polyurethane and polyethylene; and / or, the insulating layer includes an insulating region; the insulating region includes EVA and / or adhesive; the support layer includes a first pigment layer, a PET layer and a second pigment layer stacked sequentially; and / or, the thickness of the support layer is 90-200 μm; and / or, the thickness of the insulating layer is 50-100 μm; and / or, the thickness of the conductive layer is 30-100 μm.
[0011] According to another aspect of the present invention, a method for preparing the above-mentioned conductive backplate is provided, the method comprising: step S1, coating a conductive material onto a support layer and then curing it to form a conductive layer on the surface of the support layer; and step S2, bonding an insulating layer to the surface of the conductive layer away from the support layer to obtain a conductive backplate.
[0012] Furthermore, the curing temperature is 130–150°C, and / or the curing time is 5–10 min.
[0013] Further, the method for preparing the conductive material includes: dividing the solvent into two parts to obtain solvent A and solvent B; mixing the raw materials including the matrix resin and solvent A to obtain a first mixture; mixing the raw materials including conductive filler, solvent B and additives and then sequentially impregnating them in a polymer resin containing a third solvent and stirring to obtain a second mixture; mixing the raw materials including the first mixture, the second mixture and a curing agent to obtain the conductive material; wherein the impregnation time is 20 to 40 minutes; and the stirring speed is 1000 to 1500 rpm.
[0014] According to another aspect of the present invention, a photovoltaic module is provided, comprising solar cells and a backsheet, the backsheet being the conductive backsheet described above.
[0015] By applying the technical solution of this invention, the conductive backsheet of this application optimizes the composition of the conductive material in the conductive layer, enabling the conductive layer to have good ductility, better match with the thermal properties of the polymer, and better composite with the support layer. It also improves the conductivity, mechanical strength, and weather resistance of the conductive backsheet, thereby increasing the photoelectric conversion efficiency of the photovoltaic module. Specifically, adding a matrix resin to the conductive material not only binds the conductive filler and other components together to form a continuous film or coating, thus better compositing with the support layer and preventing the conductive layer from delaminating or peeling off during processing and use, but also serves as a dispersion medium to uniformly disperse the conductive filler, avoiding agglomeration and improving the uniformity and conductivity of the conductive network. Adding conductive materials improves the ductility and conductivity of the conductive layer and allows for better matching with the thermal properties of the polymer. Metal particles have low resistivity, and their use is preferred to form a conductive network, thereby achieving high conductivity in the conductive layer. The preferred use of metal oxides can improve the conductivity of the conductive layer and also enhance its stability, such as oxidation and corrosion resistance. Fiber-based materials are preferred due to their high aspect ratio, enabling them to form bridging structures within the conductive layer. This enhances the continuity and stability of the conductive network, while also improving the strength and flexibility of the conductive layer, making it less prone to damage under stress and maintaining good conductivity. Carbon-based materials possess excellent conductivity and chemical stability, enabling the formation of highly efficient conductive networks, thereby improving the conductivity and durability of the conductive layer. Mica exhibits good insulation and mechanical strength; by coating its surface with a metal layer, mica can be transformed into a conductive filler with both insulating and conductive properties. Preferably, mica materials with a metal surface layer are used to increase the mechanical strength of the conductive layer while providing additional conductive paths, thus improving the overall performance of the conductive layer. Adding a curing agent not only promotes the curing and cross-linking of the matrix resin but also improves the hardness, strength, and toughness of the conductive layer. Attached Figure Description
[0016] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0017] Figure 1 A schematic diagram of the conductive backplate in Embodiment 1 of this application is shown.
[0018] The above figures include the following reference numerals:
[0019] 1. Support layer; 2. Conductive layer; 3. Insulating layer. Detailed Implementation
[0020] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0021] As analyzed in the background section of this application, the existing conductive backsheet has problems such as poor ductility, mismatch with the thermal properties of polymers, and poor adhesion, resulting in poor photoelectric conversion efficiency of photovoltaic modules. In order to solve the above problems, this application provides a conductive backsheet, its preparation method, and a photovoltaic module.
[0022] In a typical embodiment of this application, a conductive backsheet is provided, comprising a support layer, a conductive layer, and an insulating layer stacked sequentially. The conductive layer includes a conductive circuit region, which includes a conductive material, which is a conductive adhesive and / or a conductive coating. By weight, the conductive material comprises: 20-40 parts of a matrix resin, 50-80 parts of a conductive filler, and 5-10 parts of a curing agent. The conductive filler is selected from any one or more of metal particles, metal oxides, fibrous materials, carbon-based materials, polythiophene polymers, and mica materials with a metal layer on their surface.
[0023] The conductive backsheet of this application optimizes the composition of the conductive material in the conductive layer, resulting in a conductive layer with good ductility, better matching with the thermal properties of the polymer, and better composite with the support layer. It also improves the conductivity, mechanical strength, and weather resistance of the conductive backsheet, thereby increasing the photoelectric conversion efficiency of the photovoltaic module. Specifically, adding a matrix resin to the conductive material not only binds the conductive filler and other components together to form a continuous film or coating, thus better compositing with the support layer and preventing delamination or peeling of the conductive layer during processing and use, but also serves as a dispersion medium, ensuring uniform dispersion of the conductive filler and preventing agglomeration, thereby improving the uniformity and conductivity of the conductive network. Adding conductive materials improves the ductility and conductivity of the conductive layer and allows for better matching with the thermal properties of the polymer. Metal particles, with their low resistivity, are preferably used to form a conductive network, achieving high conductivity in the conductive layer. The preferred use of metal oxides further enhances the conductivity and stability of the conductive layer, such as oxidation and corrosion resistance. Fiber-based materials are preferred due to their high aspect ratio, enabling them to form bridging structures within the conductive layer. This enhances the continuity and stability of the conductive network, while also improving the strength and flexibility of the conductive layer, making it less prone to damage under stress and maintaining good conductivity. Carbon-based materials possess excellent conductivity and chemical stability, enabling the formation of efficient conductive networks, thereby improving the conductivity and durability of the conductive layer. Polythiophene polymers are conductive polymers with excellent conductivity; their preferred use allows for the formation of flexible and stable conductive paths, making them better suited for conductive backsheets requiring flexibility and lightweight properties. Mica possesses good insulation and mechanical strength; by coating its surface with a metal layer, mica can be transformed into a conductive filler with both insulating and conductive properties. Preferably, mica materials with a metal surface layer increase the mechanical strength of the conductive layer while providing additional conductive paths, thus improving the overall performance of the conductive layer. Adding a curing agent not only promotes the curing and cross-linking of the matrix resin but also improves the hardness, strength, and toughness of the conductive layer.
[0024] The preferred conductive material also includes 5 to 15 parts of solvent, which not only helps the conductive filler to be better dispersed in the matrix resin, thereby improving the stability and conductivity of the conductive layer, but also helps to improve the flowability and printability of the conductive material, thus enabling better and more uniform coating or printing on the surface of the support layer. The conductive material also includes 0.1 to 2 parts of additives, which help to further optimize the performance of the conductive material.
[0025] In one embodiment of this application, when the conductive material is a conductive adhesive, the conductive adhesive comprises, by weight, 20-30 parts of a first matrix resin, 60-80 parts of a first conductive filler, 5-10 parts of a first curing agent, 5-15 parts of a first solvent, and 0.1-0.5 parts of a first auxiliary agent; wherein, the first conductive filler is selected from any one or more of a first metal particle, a first carbon-based material, and a polythiophene polymer; wherein, the first metal particle is selected from any one or more of silver powder, copper powder, and nickel powder; preferably, the silver powder is spherical silver powder and / or flake silver powder, and preferably, the particle size of the silver powder is 1-5 μm; preferably, the silver-coated copper powder is silver-coated copper powder, and preferably, the copper powder is spherical copper powder; preferably, the surface of the copper powder is silver-plated or treated with anti-oxidation; the first carbon-based material is any one or more of graphene, carbon nanotubes, and conductive carbon black; the polythiophene polymer is polythiophene particles; and / or, the resistivity of the first conductive filler is 1.0 × 10⁻⁶. -8 ~3.0Ω·m, preferably 1.17×10 -8 ~2×10 -6 Ω·m.
[0026] Preferably controlling the composition and weight percentage of the conductive adhesive within the aforementioned range helps to form a dense conductive network between the first conductive fillers after the conductive adhesive dries and cures, thereby improving the conductivity of the conductive layer. Preferably controlling the resistivity of the first conductive filler within the aforementioned range helps to improve the current transmission efficiency of the conductive layer, thereby improving the photoelectric conversion efficiency of the photovoltaic module.
[0027] Optionally, the resistivity of the first conductive filler is ≤2×10⁻⁶. -6 Conductive filler with Ω·m and resistivity greater than 2×10 -6 A combination of conductive fillers with Ω·m and ≤3.0Ω·m is used.
[0028] Furthermore, the resistivity of silver-based fillers (silver powder) is 1.59 × 10⁻⁶. -8 The resistivity of copper-based filler (copper powder) is 1.17 × 10⁻⁶ Ω·m. -8 Ω·m; The resistivity of the flake-shaped silver-coated copper powder is 1.59 × 10⁻⁶ Ω·m. -6 Ω·m; the resistivity of nickel powder is 7.8 × 10⁻⁶. -8 Ω·m; the resistivity of graphene is 10 × 10⁻⁶. -8 Ω·m; the resistivity of carbon nanotubes is 10 Ω·m. -6 ~10 -7 The resistivity of polythiophene particles is 0.75–1 Ω·m.
[0029] To further improve the conductivity of the conductive adhesive, in one embodiment of this application, the first matrix resin is selected from any one or more of epoxy resin, acrylate resin, polyurethane acrylate resin, epoxy acrylate resin, polyurethane resin, polyethylene polyimide resin, silicone resin, and cyanate ester resin; and / or, the resistivity of the first matrix resin is 10 Ω·cm. 11 ~10 18 Ω·m; and / or, the first curing agent is selected from any one or more of amine curing agents, acid anhydride curing agents, imidazole curing agents, and cyanate ester curing agents; wherein, the amine curing agent is selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, m-phenylenediamine, polyamide, dicyandiamide, and amine adducts; the acid anhydride curing agent is selected from any one or more of phthalic anhydride, tetrahydrophthalic anhydride, and methylhexahydrophthalic anhydride; the imidazole curing agent is 2-ethyl-4-methylimidazolium and / or 2-methylimidazolium; and the cyanate ester curing agent is hexamethylene diisocyanate and / or diphenylmethane diisocyanate. ; and / or, the first solvent is selected from any one or more of glycidyl acrylate, butyl glycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, ethyl acetate, propylene glycol methyl ether acetate, acetone, butanone, toluene, xylene, isopropanol, butyl acetate, a mixture of dicarboxylic acid esters, cyclohexanone, 1,4-butanediol, propylene carbonate, γ-butyrolactone, dimethyl silicone oil, n-hexane, petroleum ether, perfluorohexane, hydrogenated naphthalene, and decahydronaphthalene; and / or, the first additive is selected from any one or more of the first defoamer, the first leveling agent, the first plasticizer, and the first antioxidant.
[0030] In addition, the resistivity of epoxy resin is 10. 12 ~10 18 The resistivity of acrylate resin is 10 Ω·m. 11 ~10 14 Ω·m, the resistivity of polyurethane is 10 12 ~10 15 The resistivity of polyimide resin is 10 Ω·m. 11 ~10 17 Ω·m, the resistivity of silicone is 10 12 ~10 16 Ω·m.
[0031] Preferably, the first conductive filler is a copper-based filler, and the first matrix resin is an epoxy resin. The mass ratio of the first conductive filler (copper-based filler) to the first matrix resin (epoxy resin) is 2 to 3:1, which helps the first conductive filler to better form an effective conductive network in the first matrix resin, thereby further improving the conductivity and processing performance of the conductive adhesive.
[0032] In one embodiment of this application, when the conductive material is a conductive coating, the conductive coating comprises, by weight, 30-40 parts of a second matrix resin, 50-60 parts of a second conductive filler, 5-8 parts of a second curing agent, 5-10 parts of a second solvent, and 1-2 parts of a second additive; wherein the second conductive filler is selected from any one or more of second metal particles, metal oxides, second carbon-based materials, fibrous materials, and mica materials with a metal layer on the surface; wherein the metal in the metal layer of the mica material with a metal layer on the surface is selected from any one or more of silver, powder, copper, powder, and aluminum; the second metal particles are selected from silver powder and nickel powder. The material comprises: copper powder, iron powder, aluminum powder, and aluminum foil; preferably, the silver powder is spherical and / or flake-shaped, with a particle size of 1–5 μm; preferably, the silver-coated copper powder is flake-shaped, and preferably, the copper powder is spherical; preferably, the copper powder is silver-plated or treated with an anti-oxidation agent; the metal oxide is selected from zinc oxide, lead dioxide, and tin oxide; preferably, the zinc oxide is aluminum-doped zinc oxide, and preferably, the tin oxide is antimony-doped tin oxide; the second carbon-based material is carbon black and / or graphite; the fibrous material is selected from carbon fiber, nickel fiber, copper fiber, and stainless steel fiber; and / or, the resistivity of the second conductive filler is 1.7 × 10⁻⁶. -8 ~3Ω·m, preferably 1.7×10 -8 ~1.5×10 -5 Ω·m.
[0033] Preferably controlling the composition and weight percentage of the conductive coating within the above range helps to maintain the mechanical strength and stability of the conductive layer while ensuring a low resistivity. It also helps to form a dense, uniform conductive layer that adheres well to the support layer after the conductive coating dries and cures, reducing defects such as cracks and pores, thereby improving the overall performance of the conductive layer.
[0034] Optionally, the resistivity of the second conductive filler is ≤1.5×10⁻⁶. -5 Conductive filler with Ω·m and resistivity greater than 1.5×10 -5 A combination of conductive fillers with Ω·m and ≤3.0Ω·m is used.
[0035] Conductive coatings have relatively good conductivity and simple processing technology, but relatively poor ductility, poor compatibility with polymer thermal properties, and poor adhesion. Conductive adhesives, on the other hand, have better ductility, better compatibility with polymer thermal properties, and high adhesion. It is preferable to control the conductive materials as a combination of conductive adhesive and conductive coating, with a mass ratio of conductive adhesive to conductive coating of 1:1 to 2. This helps to better balance the conductivity and mechanical strength of the conductive layer, thereby enabling the conductive backsheet to be better applied to photovoltaic modules.
[0036] To further improve the conductivity of the conductive coating, in one embodiment of this application, the second matrix resin is selected from any one or more of the following: polyacetylene resin, polyaniline resin, polypyrrole resin, polythiophene resin, ABS resin, polyvinyl alcohol resin, fluorocarbon resin, alkyd resin, epoxy resin, phenolic resin, nitrocellulose, cellulose acetate, silicone resin, urea-formaldehyde resin, polyurethane resin, polyvinyl chloride resin, acrylic resin, polyvinylidene chloride resin, polytetrafluoroethylene resin, polystyrene resin, polyethylene resin, polycarbonate resin, and polystyrene resin; and / or, the resistivity of the second matrix resin is 10 Ω·cm. -5 ~10 20 Ω·m; and / or, the second curing agent is selected from any one or more of ethylenediamine, diethylenetriamine, polyamide, Mannich base, phthalic anhydride, maleic anhydride, dicyandiamide, hexamethylene diisocyanate, isophorone diisocyanate, isophorone diisocyanate, benzoyl peroxide (BPO), diphenylphosphine oxide (TPO), 2-hydroxy-2-methylphenylacetone (1173), aminopropyltriethoxysilane (KH-550) and platinum catalyst; and / or, the second solvent is selected from any one or more of acetone, butanone, ethyl acetate, butyl acetate, ethanol, isopropanol, toluene, xylene and ethylene glycol ether; and / or, the second auxiliary agent is selected from any one or more of the second defoamer, second leveling agent, second antioxidant, second plasticizer and thixotropic agent.
[0037] Furthermore, the resistivity of the polyacetylene resin in the second matrix resin is 10. -5 ~10 -3 The resistivity of polyaniline resin is 10 Ω·m. -3 ~10 -1 The resistivity of polypyrrole resin is 1–10 Ω·m, the resistivity of polythiophene resin is 1–10 Ω·m, and the resistivity of ABS resin is 1–10 Ω·m. 16 The resistivity of polyvinyl alcohol resin is 10 Ω·m. 7 ~10 9 The resistivity of fluorocarbon resin is 10 Ω·m. 7 ~10 18 The resistivity of alkyd resin is 10 Ω·m. 7 ~10 13 Ω·m, the resistivity of epoxy resin is 10 8 ~10 14 The resistivity of phenolic resin is 10. 9 ~10 12 The resistivity of nitrocellulose is 10 Ω·m. 10 ~10 11 The resistivity of cellulose acetate is 10 Ω·m. 10 ~10 12Ω·m; the resistivity of silicone resin is 10 11 ~10 15 The resistivity of urea-formaldehyde resin is 10 Ω·m. 12 ~10 13 The resistivity of polyurethane resin is 10 Ω·m. 13 ~10 15 The resistivity of polyvinyl chloride resin is 10 Ω·m. 14 ~10 16 Ω·m, the resistivity of acrylic resin is 10 14 ~10 15 The resistivity of polyvinylidene chloride is 10 Ω·m. 14 ~10 16 The resistivity of polytetrafluoroethylene is 10 Ω·m. 15 ~10 19 The resistivity of polystyrene resin is 10. 16 ~10 20 The resistivity of polyethylene resin is 10. 16 ~10 20 The resistivity of polycarbonate resin is 10 Ω·m. 20 The resistivity of polystyrene resin is 10 Ω·m. 17 ~10 19 Ω·m.
[0038] The resistivity measurements above were obtained based on standards such as GB / T 1410, GB / T 351, GB / T 24525 and GB / T 30019.
[0039] Preferably, the first defoamer and / or the second defoamer are each independently selected from any one or more of dimethyl silicone oil, silicone emulsion, modified organosilicon, isopropanol, n-butanol, fatty acid compounds, glycerol polyether, and polyoxyethylene oxypropylene glycerol ether; the first leveling agent and / or the second leveling agent are each independently selected from any one or more of polydimethylsiloxane, modified organosilicon, silicone resin, polypropylene, fluorinated modified acrylate, fluorinated surfactant, polyether leveling agent, polyester leveling agent, and solvent leveling agent; the first antioxidant and / or the second antioxidant are each independently selected from benzotriazole, 2,6-di-tert-butyl-p-cresol, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]. The first plasticizer and / or the second plasticizer are each selected independently from one or more of the following: tetraol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, p-phenylenediamine derivative, tris[2,4-di-tert-butylphenyl]phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, dilauryl thiodipropionate, and distearate thiodipropionate; the first plasticizer and / or the second plasticizer are each selected independently from one or more of the following: dibutyl phthalate (DBP), dioctyl phthalate (DOP), epoxidized soybean oil, tricresyl phosphate, triphenyl phosphate, dioctyl sebacate, and chlorinated paraffin; the thixotropic agent is selected from one or more of the following: fumed silica, organobentonite, hydrogenated castor oil, and polyamide wax.
[0040] The preferred types of defoamers help reduce or eliminate bubbles generated during the preparation of conductive materials, thereby reducing the impact of voids on conductivity. The preferred types of leveling agents help form a smooth film on the coating surface, reducing bumps or depressions, thus improving the continuity and uniformity of the conductive layer. The preferred types of antioxidants help reduce performance degradation of the conductive backsheet due to oxidation during storage or use, thereby extending its service life. The preferred types of plasticizers help improve the flexibility of the conductive backsheet, enabling it to maintain conductivity under bending or stress conditions of photovoltaic modules. The preferred types of thixotropic agents help to better control the thixotropy of the conductive backsheet.
[0041] Preferably, the second conductive filler is a second metal particle, and the second matrix resin is an acrylic resin. The mass ratio of the second conductive filler, the second metal particle, and the second matrix resin to the acrylic resin is 1.3 to 1.8:1, which helps the second conductive filler to better form an effective conductive network in the second matrix resin, thereby further improving the conductivity and processing performance of the conductive coating.
[0042] To further improve the processing performance of the conductive material, in one embodiment of this application, the conductive material further includes a polymer resin containing a third solvent. The polymer resin containing the third solvent has a mass ratio of 35% to 45%. The third solvent is selected from any one or more of xylene, acetone, diester, propylene glycol methyl ether acetate, and ethyl acetate. The polymer resin is selected from any one or more of epoxy resin, acrylate resin, polyurethane acrylate resin, epoxy acrylate resin, polyimide resin, polyurethane, and polyethylene.
[0043] In one embodiment of this application, the insulating layer includes an insulating region; the insulating region includes EVA (ethylene-vinyl acetate copolymer) and / or an adhesive; the support layer includes a first pigment layer, a PET layer and a second pigment layer stacked sequentially; and / or, the thickness of the support layer is 90-200 μm; and / or, the thickness of the insulating layer is 50-100 μm; and / or, the thickness of the conductive layer is 30-100 μm.
[0044] The insulating layer includes insulating regions distributed in areas where conductivity is not required, ensuring that the normal function of the conductive layer is not interfered with. During the coating or printing process of the conductive material, the insulating regions are formed by coating dried EVA or adhesive, contributing to good insulation and overall structural stability.
[0045] Preferably, the support layer employs the above-described structure. The first and second pigment layers contain pigments, and preferably, each pigment in the first and second pigment layers is independently selected from one or more of titanium dioxide, zinc oxide, carbon black, azo pigments, phthalocyanine pigments, infrared-reflecting pigments, and ultraviolet-absorbing pigments. This helps enhance the aesthetic appearance of the conductive backsheet and protect the PET layer from external environmental damage, such as ultraviolet radiation and physical abrasion. The PET layer (polyethylene terephthalate) serves as the core of the support layer, providing the necessary mechanical strength and thermal stability for the backsheet.
[0046] Preferably controlling the thickness of the support layer within the aforementioned range helps improve the mechanical properties of the conductive backsheet, including tensile strength, flexural strength, and overall structural stability. Preferably controlling the thickness of the insulating layer within the aforementioned range helps provide sufficient insulation resistance. Preferably controlling the thickness of the conductive layer within the aforementioned range helps provide stable electrical conductivity, reduces contact resistance, and thereby improves the photoelectric conversion efficiency of the photovoltaic module.
[0047] In another typical embodiment of this application, a method for preparing the above-mentioned conductive backplate is provided. The method includes: step S1, coating a conductive material onto a support layer and then curing it to form a conductive layer on the surface of the support layer; and step S2, bonding an insulating layer to the surface of the conductive layer away from the support layer to obtain a conductive backplate.
[0048] The conductive backsheet preparation method of this application can efficiently produce conductive backsheets that meet the requirements of photovoltaic modules. The conductive backsheet has excellent conductivity, reliable electrical insulation and sufficient mechanical strength, while ensuring good adhesion between the layers of materials to form a stable composite structure.
[0049] In addition, the preparation method of the conductive backplane also includes processing the conductive adhesive into a graphic circuit by screen printing, then coating it onto the surface of the support layer, setting conductive ports at the endpoints of the conductive line area, heating to 100-110°C and drying for 2-3 minutes, coating the surface of the conductive layer away from the support layer with an adhesive insulating layer, heating to 110-120°C and drying for 2-4 minutes, and then removing the dry adhesive at the conductive ports to obtain the conductive backplane.
[0050] In one embodiment of this application, the curing temperature is 130–150°C, and / or the curing time is 5–10 min.
[0051] Preferably controlling the curing temperature and time within the above range helps to promote the cross-linking reaction between the matrix resin and the curing agent, thereby forming a stable, dense conductive layer with good electrical conductivity, and better adhering to the surface of the support layer.
[0052] In one embodiment of this application, the method for preparing a conductive material includes: dividing a solvent into two parts to obtain solvent A and solvent B; mixing raw materials including a matrix resin and solvent A to obtain a first mixture; mixing raw materials including conductive filler, solvent B and additives and then sequentially impregnating them in a polymer resin containing a third solvent and stirring to obtain a second mixture; mixing raw materials including the first mixture, the second mixture and a curing agent to obtain a conductive material; wherein the impregnation time is 20 to 40 minutes; and the stirring speed is 1000 to 1500 rpm.
[0053] Dividing the total solvent volume into two parts and adding the solvent in stages helps to better control the viscosity of the conductive material and the dispersibility of the filler, reducing the decrease in material stability caused by adding too much solvent at once. Mixing the matrix resin with solvent A helps the matrix resin to be fully dispersed in the solvent, forming a homogeneous first mixture, which facilitates subsequent bonding with the conductive filler. After mixing the conductive filler, solvent B, and additives, the mixture is impregnated in a polymer resin containing a third solvent, preferably with the impregnation time controlled within the aforementioned range, which helps to improve the dispersibility of the conductive filler and reduce agglomeration. Subsequently, the conductive filler is further dispersed by high-speed stirring to form a second mixture. Mixing the first mixture, the second mixture, and the curing agent helps to achieve a uniform distribution of the conductive filler and curing agent in the matrix resin.
[0054] In another typical embodiment of this application, a photovoltaic module is provided, including solar cells and a backsheet, wherein the backsheet is the aforementioned conductive backsheet.
[0055] Photovoltaic modules using the aforementioned conductive backsheet exhibit excellent conductivity, mechanical strength, and weather resistance, thereby improving the photoelectric conversion efficiency of the photovoltaic modules. Preferably, the endpoints of the conductive lines in the conductive layer are provided with protruding conductive interfaces that connect with the photovoltaic module.
[0056] The beneficial effects of this application will be further illustrated below with reference to the embodiments.
[0057] Example 1
[0058] The conductive material is a conductive adhesive. By weight, the raw materials of the conductive adhesive are: 25 parts of the first matrix resin, epoxy resin E-51; 70 parts of the first conductive filler, flake silver powder; 7 parts of the first curing agent, ethylenediamine; 10 parts of the first solvent, acetone; and 0.3 parts of the auxiliary agent, defoamer, dimethyl silicone oil. The resistivity of the first matrix resin, epoxy resin E-51, is 10 Ω·cm. 14 The resistivity of the first conductive filler, the flake silver powder, is 1.59 × 10 Ω·m. -8 Ω·m.
[0059] Preparation of conductive adhesive: The first solvent is divided into two parts, resulting in 5 parts of solvent A (acetone) and 5 parts of solvent B (acetone). The first matrix resin and solvent A (acetone) are mixed to obtain the first mixture. The first conductive filler, solvent B (acetone), and additives are mixed and sequentially impregnated in a polymer resin (polyethylene resin, acetone content 40% by mass) containing acetone for 30 minutes, and stirred at 1200 rpm to obtain the second mixture. The first mixture, the second mixture, and the curing agent are mixed to obtain the conductive adhesive.
[0060] Fabrication of the conductive backsheet: Conductive adhesive was applied to a 150mm thick CPC structure backsheet using a wire rod, and then the backsheet was placed in an oven and cured at 150℃ for 5 minutes, forming a 40mm thick conductive layer on the surface of the support layer. In areas requiring insulation, an 80mm thick EVA insulating layer was attached to the surface of the conductive layer away from the support layer, thus obtaining the conductive backsheet. The conductive backsheet consists of a support layer 1, a conductive layer 2, and an insulating layer 3 stacked sequentially, as shown in the diagram. Figure 1 As shown.
[0061] Example 2
[0062] The difference from Example 1 is that, by weight, the conductive adhesive comprises 30 parts of a first matrix resin, epoxy resin E-51; 80 parts of a first conductive filler, flake-shaped silver-coated copper powder; 10 parts of a first curing agent, phthalic anhydride; 15 parts of a first solvent, ethyl acetate; and 0.1 parts of an auxiliary agent, antioxidant benzotriazole. The resistivity of the first matrix resin, epoxy resin E-51, is 10 Ω·cm. 14 The resistivity of the first conductive filler, flake-shaped silver-coated copper powder, is 1.59 × 10 Ω·m. -6 Ω·m, ultimately yielding conductive adhesive.
[0063] Preparation of conductive backplate: The curing temperature is 130℃, and the conductive backplate is finally obtained.
[0064] Example 3
[0065] The difference from Example 2 is that, by weight, the conductive adhesive comprises 20 parts of a first matrix resin (acrylate resin), 60 parts of a first conductive filler (nickel powder), 5 parts of a first curing agent (hexamethylene diisocyanate), 5 parts of a first solvent (glycidyl acrylate), 0.2 parts of a plasticizer (dibutyl phthalate), and 0.3 parts of a defoamer (dimethyl silicone oil). The resistivity of the first matrix resin (acrylate resin) is 10 Ω·cm. 13 The resistivity of the first conductive filler, nickel powder, is 7.8 × 10 Ω·m. -8 Ω·m, ultimately yielding conductive adhesive and conductive backplate.
[0066] Example 4
[0067] The difference from Example 2 is that, by weight, the conductive adhesive consists of 20 parts of a first matrix resin (silicone resin), 65 parts of a first conductive filler (15 parts of carbon nanotubes and 40 parts of conductive carbon black), 5 parts of a first curing agent (hexamethylene diisocyanate), 5 parts of a first solvent (glycidyl acrylate), and 0.2 parts of an auxiliary agent (defoamer, dimethyl silicone oil). The resistivity of the first matrix resin (silicone resin) is 10 Ω·cm. 16 The resistivity of the first conductive filler, carbon nanotubes, is 10 × 10 Ω·m. -6 The resistivity of conductive carbon black is 2.5 Ω·m, which ultimately yields conductive adhesive and conductive backsheet.
[0068] Example 5
[0069] The difference from Example 1 is that the first matrix resin is epoxy resin E-51 and the first conductive filler is flake-shaped silver-coated copper powder. The total weight of the first matrix resin and the first conductive filler is 95 parts, and the mass ratio of the first matrix resin to the first conductive filler is 1:2. The resistivity of the first matrix resin, epoxy resin E-51, is 10 Ω·cm. 14 The resistivity of the first conductive filler, flake-shaped silver-coated copper powder, is 1.59 × 10 Ω·m.-6 Ω·m, ultimately yielding conductive adhesive and conductive backplate.
[0070] Example 6
[0071] The difference from Example 1 is that the first matrix resin is epoxy resin E-51 and the first conductive filler is flake-shaped silver-coated copper powder. The total weight of the first matrix resin and the first conductive filler is 95 parts, and the mass ratio of the first matrix resin to the first conductive filler is 1:3.5. The resistivity of the first matrix resin, epoxy resin E-51, is 10 ohms. 14 The resistivity of the first conductive filler, flake-shaped silver-coated copper powder, is 1.59 × 10 Ω·m. -6 Ω·m, ultimately yielding conductive adhesive and conductive backplate.
[0072] Example 7
[0073] The conductive material is a conductive coating. By weight, the raw materials of the conductive coating are: 35 parts of the second matrix resin (phenolic resin), 55 parts of the second conductive filler (graphite), 6 parts of the second curing agent (maleic anhydride), 8 parts of the second solvent (xylene), and 0.5 parts of the auxiliary agents (leveling agent polydimethylsiloxane, dimethyl silicone oil as defoamer, and dibutyl phthalate as plasticizer). The resistivity of the second matrix resin (phenolic resin) is 10 Ω·cm. 11 The resistivity of the second conductive filler, graphite, is 8 × 10 Ω·m. -6 Ω·m.
[0074] Preparation of conductive coating: The second solvent is divided into two parts, resulting in 4 parts of solvent A xylene and 4 parts of solvent B xylene. The second matrix resin and solvent A xylene are mixed to obtain the first mixture. The mixture of the second conductive filler, solvent B xylene, and additives is sequentially impregnated in a polymer resin containing xylene (epoxy resin E-51, xylene mass percentage 40%) for 30 min, and stirred at 1200 rpm to obtain the second mixture. The first mixture, the second mixture, and the curing agent are mixed to obtain the conductive coating.
[0075] Fabrication of the conductive backsheet: Conductive coating was applied to a 90mm thick CPC (Chip-Polymer) support layer backsheet using a wire rod, and then the backsheet was placed in an oven and cured at 130°C for 5 minutes, forming a 50mm thick conductive layer on the surface of the support layer. In areas requiring insulation, a 30mm thick EVA insulating layer was attached to the surface of the conductive layer away from the support layer, thus obtaining the conductive backsheet. The conductive backsheet consists of a support layer, a conductive layer, and an insulating layer stacked sequentially.
[0076] Example 8
[0077] The difference from Example 7 is that, by weight, the conductive coating consists of 40 parts of a second matrix resin (30 parts of acrylic resin and 10 parts of epoxy resin E-51), 60 parts of a second conductive filler (silver powder), 8 parts of a second curing agent (Mannich base), 10 parts of a second solvent (butyl acetate), 0.5 parts of an additive (leveling agent (polydimethylsiloxane)), 0.5 parts of an defoamer (dimethyl silicone oil), and 0.5 parts of a plasticizer (dibutyl phthalate). The resistivity of the acrylic resin in the second matrix resin is 10 Ω·cm. 14 The resistivity of epoxy resin E-51 is 10 Ω·m. 14 The resistivity of the second conductive filler, silver powder, is 1.59 × 10 Ω·m. -8 Ω·m, ultimately yielding a conductive coating.
[0078] Preparation of conductive backplate: The curing temperature is 130℃ and the curing time is 5min, and the conductive backplate is finally obtained.
[0079] Example 9
[0080] The difference from Example 7 is that, by weight, the conductive coating consists of 30 parts of a second matrix resin (acrylic resin), 50 parts of a second conductive filler (silver-coated copper powder), 5 parts of a second curing agent (Mannich base), 5 parts of a second solvent (ethyl acetate), and 1 part of an auxiliary antioxidant (benzotriazole). The resistivity of the second matrix resin (acrylic resin) is 10⁻⁶ Ω·cm. 15 The resistivity of the second conductive filler, silver-coated copper powder, is 1.59 × 10 Ω·m. -6 Ω·m, ultimately yielding a conductive coating.
[0081] Preparation of conductive backplate: The curing temperature is 130℃ and the curing time is 5min, and the conductive backplate is finally obtained.
[0082] Example 10
[0083] The difference from Example 7 is that, by weight, the conductive coating consists of 40 parts of a second matrix resin (polyaniline resin), 50 parts of a second conductive filler (45 parts of carbon black and 5 parts of carbon fiber), 6 parts of a second curing agent (Mannich base), 6 parts of a second solvent (xylene), and 1.2 parts of an additive antioxidant (benzotriazole). The resistivity of the second matrix resin (polyaniline resin) is 10 Ω·cm. -2 The resistivity of the second conductive filler, carbon black, is 2.5 Ω·m, and the resistivity of carbon fiber is 1.428 × 10⁻⁶ Ω·m. -5 Ω·m, ultimately yielding a conductive coating.
[0084] Preparation of conductive backsheet: The curing temperature is 150℃ and the curing time is 5min, and finally a conductive backsheet is obtained.
[0085] Example 11
[0086] The difference from Example 7 is that the second matrix resin is acrylic resin and the second conductive filler is silver-coated copper powder. The total weight of the second matrix resin and the second conductive filler is 90 parts, and the mass ratio of the second matrix resin to the second conductive filler is 1:1.8. The resistivity of the second matrix resin, acrylic resin, is 10 Ω·cm. 14 The resistivity of the second conductive filler, silver-coated copper powder, is 1.59 × 10 Ω·m. -6 Ω·m, ultimately yielding conductive adhesive and conductive backplate.
[0087] Example 12
[0088] The difference from Example 7 is that the second matrix resin is acrylic resin and the second conductive filler is silver-coated copper powder. The total weight of the second matrix resin and the second conductive filler is 90 parts, and the mass ratio of the second matrix resin to the second conductive filler is 1:2. The resistivity of the second matrix resin, acrylic resin, is 10 Ω·cm. 14 The resistivity of the second conductive filler, silver-coated copper powder, is 1.59 × 10 Ω·m. -6 Ω·m, ultimately yielding conductive adhesive and conductive backplate.
[0089] Example 13
[0090] The difference from Example 1 is that the curing temperature is 150°C and the curing time is 10 minutes, resulting in a conductive backplate.
[0091] Example 14
[0092] The difference from Example 1 is that the curing temperature is 120°C and the curing time is 13 minutes, resulting in a conductive backplate.
[0093] Example 15
[0094] The difference from Example 1 is that the thickness of the support layer is 200 μm, the thickness of the insulating layer is 100 μm, and the thickness of the conductive layer is 100 μm, resulting in a conductive backplate.
[0095] Example 16
[0096] The difference from Example 1 is that the thickness of the support layer is 90 μm, the thickness of the insulating layer is 40 μm, and the thickness of the conductive layer is 20 μm, resulting in a conductive backplate.
[0097] Example 17
[0098] The difference from Example 1 is that the total weight of the conductive material is 109 parts, and the conductive material is the conductive adhesive in Example 1 and the conductive coating in Example 7. The mass ratio of the conductive adhesive to the conductive coating is 1:1, and a conductive backplate is finally obtained.
[0099] Example 18
[0100] The difference from Example 1 is that the total weight of the conductive material is 109 parts, and the conductive material is the conductive adhesive in Example 1 and the conductive coating in Example 7. The mass ratio of the conductive adhesive to the conductive coating is 1:3, and a conductive backplate is finally obtained.
[0101] Comparative Example 1
[0102] The difference from Example 1 is that the conductive layer is only a silver metal layer, resulting in a conductive backplate.
[0103] Comparative Example 2
[0104] The difference from Example 1 is that, by weight, the raw materials for the conductive adhesive are 45 parts of the first matrix resin epoxy resin E-51, 90 parts of the first conductive filler flake silver powder, 15 parts of the first curing agent ethylenediamine, 10 parts of the first solvent acetone, and 3 parts of the auxiliary agent defoamer dimethyl silicone oil, ultimately yielding the conductive adhesive and the conductive backplate.
[0105] Comparative Example 3
[0106] The difference from Example 7 is that, by weight, the raw materials for the conductive coating are 15 parts of the second matrix resin phenolic resin, 45 parts of the second conductive filler graphite, 3 parts of the second curing agent maleic anhydride, and 3 parts of the second solvent xylene, ultimately yielding conductive adhesive and conductive backsheet.
[0107] Test method:
[0108] Photovoltaic module fabrication: The structure of a photovoltaic module, from bottom to top, consists of a glass layer, an encapsulant layer, a BC cell layer, a perforated encapsulant layer, and a conductive backsheet layer. After fabrication, the module is placed in a laminator and laminated at 145°C or 150°C to obtain a laminated component.
[0109] Mechanical strength: The elongation at break and tensile strength were tested using a universal testing tensile testing machine.
[0110] Weather resistance: The test measures the peel force between the conductive backing and the adhesive film of the laminate before aging; the test measures the color value of the laminate before and after PCT48h. PCT48h refers to a high-pressure boiling test (PCT48h) conducted for 48 hours in an environment with a high temperature of 121℃, a high humidity of 100%RH, and a temperature of 2atm.
[0111] Electrical conductivity: The resistivity of the sample was tested using the four-probe method.
[0112] The test results are shown in Table 1.
[0113] Table 1
[0114]
[0115]
[0116] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:
[0117] The conductive backsheet of this application optimizes the composition of the conductive material in the conductive layer, resulting in a conductive layer with good ductility, better matching with the thermal properties of the polymer, and better composite with the support layer. It also improves the conductivity, mechanical strength, and weather resistance of the conductive backsheet, thereby increasing the photoelectric conversion efficiency of the photovoltaic module. Specifically, adding a matrix resin to the conductive material not only binds the conductive filler and other components together to form a continuous film or coating, thus better compositing with the support layer and preventing delamination or peeling of the conductive layer during processing and use, but also serves as a dispersion medium, ensuring uniform dispersion of the conductive filler and preventing agglomeration, thereby improving the uniformity and conductivity of the conductive network. Adding conductive materials improves the ductility and conductivity of the conductive layer and allows for better matching with the thermal properties of the polymer. Metal particles, with their low resistivity, are preferably used to form a conductive network, achieving high conductivity in the conductive layer. The preferred use of metal oxides further enhances the conductivity and stability of the conductive layer, such as oxidation and corrosion resistance. Fiber-based materials are preferred due to their high aspect ratio, enabling them to form bridging structures within the conductive layer. This enhances the continuity and stability of the conductive network, while also improving the strength and flexibility of the conductive layer, making it less prone to damage under stress and maintaining good conductivity. Carbon-based materials possess excellent conductivity and chemical stability, enabling the formation of efficient conductive networks, thereby improving the conductivity and durability of the conductive layer. Polythiophene polymers are conductive polymers with excellent conductivity; their preferred use allows for the formation of flexible and stable conductive paths, making them better suited for conductive backsheets requiring flexibility and lightweight properties. Mica possesses good insulation and mechanical strength; by coating its surface with a metal layer, mica can be transformed into a conductive filler with both insulating and conductive properties. Preferably, mica materials with a metal surface layer increase the mechanical strength of the conductive layer while providing additional conductive paths, thus improving the overall performance of the conductive layer. Adding a curing agent not only promotes the curing and cross-linking of the matrix resin but also improves the hardness, strength, and toughness of the conductive layer.
[0118] The above are merely embodiments of the present invention and are not intended to limit the invention. Those skilled in the art will recognize that the present invention can be modified and varied in various ways. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. An electrically conductive backsheet comprising a support layer, an electrically conductive layer and an insulating layer, which are stacked in that order, the electrically conductive layer comprising an electrically conductive circuit area, the electrically conductive circuit area comprising an electrically conductive material, characterized in that, The conductive material is a conductive glue and / or a conductive paint; The conductive material comprises, in parts by weight: 20-40 parts of a base resin; 50-80 parts of a conductive filler; and 5-10 parts of a curing agent; The conductive filler is selected from any one or more of metal particles, metal oxides, fiber materials, carbon-based materials, polythiophene polymers, and mica materials with a metal layer on the surface.
2. The conductive backplane of claim 1, wherein, When the conductive material is the conductive glue, the conductive glue comprises, in parts by weight: 20-30 parts of a first base resin; 60-80 parts of a first conductive filler; 5-10 parts of a first curing agent; 5-15 parts of a first solvent; and 0.1-0.5 parts of a first auxiliary agent; The first conductive filler is selected from any one or more of first metal particles, first carbon-based materials, and the polythiophene polymers; the first metal particles are selected from any one or more of silver powder, copper powder, and nickel powder; the first carbon-based materials are selected from any one or more of graphene, carbon nanotubes, and conductive carbon black; and the polythiophene polymers are polythiophene particles; and / or the first electrically conductive filler has a resistivity of 1.0 x 10 -8 ~ 3.0 Ω-m, preferably 1.17 x 10 -8 ~ 2 x 10 -6 Ω-m.
3. The conductive backplane of claim 2, wherein, The first base resin is selected from any one or more of an epoxy resin, an acrylate resin, a polyurethane acrylate resin, an epoxy acrylate resin, a polyurethane resin, a polyvinyl polyimide resin, a silicone resin, and a cyanate ester resin; and / or, the first base resin has a resistivity of 10 11 ~ 10 18 Ω-m; The first curing agent is selected from any one or more of amine curing agents, acid anhydride curing agents, imidazole curing agents, and cyanate curing agents; the amine curing agents are selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, m-phenylenediamine, polyamide, dicyandiamide, and amine adducts; the acid anhydride curing agents are selected from any one or more of phthalic anhydride, tetrahydrophthalic anhydride, and methylhexahydrophthalic anhydride; the imidazole curing agents are 2-ethyl-4-methylimidazole and / or 2-methylimidazole; and the cyanate curing agents are hexamethylene diisocyanate and / or diphenylmethane diisocyanate; The first solvent is selected from any one or more of glycidyl acrylate, butyl glycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, ethyl acetate, propylene glycol methyl ether acetate, acetone, butanone, toluene, xylene, isopropyl alcohol, butyl acetate, dibasic acid ester mixture, cyclohexanone, 1,4-butanediol, propylene carbonate, gamma-butyrolactone, dimethyl silicone oil, n-hexane, petroleum ether, perfluorohexane, hydrogenated naphthalene, and decalin; The first auxiliary agent is selected from any one or more of a first defoaming agent, a first leveling agent, a first plasticizer, and a first antioxidant.
4. The conductive backplane of claim 1, wherein, When the conductive material is the conductive paint, the conductive paint comprises, in parts by weight: 30-40 parts of a second base resin; 50-60 parts of a second conductive filler; 5-8 parts of a second curing agent; 5-10 parts of a second solvent; and 1-2 parts of a second auxiliary agent; The second conductive filler is selected from any one or more of a second metal particle, the metal oxide, a second carbon-based material, the fibrous material, and the mica material containing a metal layer on the surface; the second metal particle is selected from any one or more of silver powder, nickel powder, copper powder, iron powder, aluminum powder, and aluminum foil; the metal oxide is selected from any one or more of zinc oxide, lead dioxide, and tin oxide; the second carbon-based material is carbon black and / or graphite; and the fibrous material is selected from any one or more of carbon fiber, nickel fiber, copper fiber, and stainless steel fiber; and / or the second electrically conductive filler has an electrical resistivity of 1.7 x 10 -8 ~ 3 Ω-m, preferably 1.7 x 10 -8 ~ 1.5 x 10 -5 Ω-m.
5. The conductive backplane of claim 4, wherein, The second matrix resin is selected from any one or more of polyacetylene resin, polyaniline resin, polypyrrole resin, polythiophene resin, ABS resin, polyvinyl alcohol resin, fluorocarbon resin, alkyd resin, epoxy resin, phenolic resin, nitrocellulose, cellulose acetate, silicone resin, urea-formaldehyde resin, polyurethane resin, polyvinyl chloride resin, acrylic resin, polyvinylidene chloride resin, polytetrafluoroethylene resin, polystyrene resin, polyethylene resin, polycarbonate resin, and polystyrene resin; and / or, the resistivity of the second matrix resin is 10 Ω·cm. -5 ~10 20 Ω·m; The second curing agent is selected from any one or more of ethylenediamine, diethylenetriamine, polyamide, Mannich base, phthalic anhydride, maleic anhydride, dicyandiamide, hexamethylene diisocyanate, isophorone diisocyanate, isophorone diisocyanate, benzoyl peroxide, diphenyl phosphine oxide, 2-hydroxy-2-methylpropiophenone, aminopropyl triethoxysilane, and platinum gold catalyst; The second solvent is selected from any one or more of acetone, butanone, ethyl acetate, butyl acetate, ethanol, isopropyl alcohol, toluene, xylene, and glycol ether; The second auxiliary agent is selected from any one or more of a second defoaming agent, a second leveling agent, a second antioxidant, a second plasticizer, and a thixotropic agent.
6. The conductive backplane of any of claims 1 to 5, wherein, The conductive material further comprises a polymer resin containing a third solvent, the mass fraction of the third solvent in the polymer resin being 35-45%, the third solvent being selected from any one or more of xylene, acetone, dibasic acid ester, propylene glycol methyl ether acetate, and ethyl acetate, and the polymer resin being selected from any one or more of epoxy resin, acrylate resin, polyurethane acrylate resin, epoxy acrylate resin, polyimide resin, polyurethane, and polyethylene; The insulating layer comprises an insulating region; the insulating region comprises EVA and / or adhesive; the support layer comprises a first pigment layer, a PET layer, and a second pigment layer stacked in sequence; The thickness of the support layer is 90-200 μm; the thickness of the insulating layer is 50-100 μm; and the thickness of the conductive layer is 30-100 μm.
7. A method of producing the conductive back sheet according to any one of claims 1 to 6, characterized by, The preparation method comprises: Step S1, curing the conductive material after being coated on the support layer to form a conductive layer on the surface of the support layer; and Step S2, bonding the insulating layer to the surface of the conductive layer away from the support layer to obtain a conductive backboard.
8. The preparation method according to claim 7, characterized in that, The curing temperature is 130-150°C, and / or the curing time is 5-10 min.
9. The production method according to claim 7 or 8, characterized by, The preparation method of the conductive material comprises: The solvent is divided into two parts to obtain solvent A and solvent B; Raw materials including a base resin and the solvent A are mixed to obtain a first mixture; Raw materials including a conductive filler, the solvent B, and an auxiliary agent are mixed and then sequentially infiltrated in a polymer resin containing a third solvent and stirred to obtain a second mixture; Raw materials including the first mixture, the second mixture, and a curing agent are mixed to obtain the conductive material; The infiltration time is 20-40 min, and the stirring speed is 1000-1500 rpm.
10. A photovoltaic module comprising solar cells and a backsheet, characterized in that, The back sheet is the conductive back sheet of any one of claims 1 to 6.
Citation Information
Cited By
Coating composition, local conductive and insulating bifunctional backboard for back contact battery, and preparation method and application of local conductive and insulating bifunctional backboard
CN122302704A